Design innovation of fish cooling system using liquefied petroleum gas fuel. Issue 1 (May 2020) - Kadhafi, M; Sunardi,; Nurdiani, R; Baidowi, A; Wardhana, E M
Abstract: Fresh fish is known as one of the highly perishable foods. Losses in the primary fish harbor and seafood production are significant, with discarding rates between 9-15%, and more losses occur during fresh fish distribution. This research was an effort to provide better fresh fish distribution equipment using a refrigerator cooling system with Liquefied Petroleum Gas (LPG) fuel generator as a power source. LPG was chosen because it is more economical and profitable than gasoline. Based on fuel consumption, LPC was40.71% lower than premium gasoline, 62.63% lower than pertamax gasoline, and 64.85% lower than pertamax plus gasoline. The calculation of refrigeration heat load was carried out by applying heat transfer theory. Since the refrigeration heat load obtained was 310 Watt, then the type and capacity of the generator was easily determined.